Bioefficacy and evaluation of newer insecticides against whitefly in castor: Bioefficacy and evaluation of newer insecticides against whitefly in castor - B GEETHA; M SENTHILKUMAR; M DEIVAMANI; S RVENKATACHALAM (Journal of Oilseeds Research, 2020)
Castor is attacked by several sucking pests. Among them, whitefly, Trialeurodes ricini is the major pest during rabi season resulting in extensive losses in the yield. A field trial was conducted to evaluate the bio-efficacy of seven newer insecticides for the management of whitefly. After two rounds of spraying, the pooled mean population of whiteflies was lowest in the treatment profenophos 50EC @ 2 ml/l followed by buprofezin 25SC @ 1.5 ml/l. Reduction of whitefly population over control indicated that buprofezin 25SC @ 1.5 ml/l reduced the whiteflies population up to 71.2% followed by profenophos 50EC @ 2 ml/l (67.5% reduction over control).